Cloud-based solutions used by hungarian SMEs and analysis of its effects - Horváth Ádám Béla (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2023)
Abstract. The wide range of technological innovations took place in the post-millennium period and later became widely available have fundamentally reshaped the relationship between ICT infrastructure and business in the life of for-profit organizations. This is particularly true for the socalled primary (value-creating) processes. These technologies that have fundamentally transformed the way business organizations operate are collectively referred to as "Industry 4.0" technologies. A significant group of these technologies are the cloud-based solutions. By using these solutions, the users can get benefits from the ICT infrastructure through a third-party service. These services can be applications made available on a specific online interface (SaaS), or various platform elements (PaaS, for example: application servers, virtual servers, etc.) or infrastructure elements such as leased computing capacity (IaaS). By using cloud-based solutions, the customer can avoid the investment needed to run the ICT infrastructure and the additional problems rooted by the operation of ICTinfrastructure. A questionnaire survey was carried out in early 2019, in which 498 respondents voluntarily participated. The survey investigated the deployment level of ICT infrastructure among SMEs in Hungary, its information security consequences and how the management of the for-profit organizations evaluate the contribution of ICT infrastructure to the success of their business. The use of different cloud-based solutions was also measured in the mentioned questionnaire. The paper presents the research results of the prevalence of use of different cloud solutions with similar studies in the region. Furthermore, it examines whether cloud solutions have individually detectable beneficial effects on business operations, and whether synergies can be identified when multiple cloud applications are used together. Based on the qualitative results of the research and their interpretation, a broader analysis has been offered.

Az ezredfordulót követő időszakban végbemenő és később általánosan elérhető technológiai innovációk széles köre alapvetően alakította át a gazdálkodó szervetek életében az IKTinfrastruktúra és a üzleti tevékenység viszonyát. Különös tekintettel igaz ez az úgynevezett elsődleges (értékteremtő) folyamatokra. Ezeket a gazdálkodó szervezetek működését alapjaiban átalakító technológiát összefoglaló névvel „IPAR 4.0”-technológiáknak nevezzük. Ezen technológiák egyik jelentős-csoportja az un. felhőalapú technológiák, amelynek alkalmazása révén az igénybe vevő fél egy harmadik fél által nyújtott szolgáltatás révén használja az IKT-infrastruktúra által biztosított előnyöket. Ezek a szolgáltatások lehetnek egy adott online felületen elérhetővé tett alkalmazások (SaaS), különféle platform elemek (PaaS, ezekre példák az alkalmazás szerverek, virtuális szerverek stb.), vagy infrastrukturális elemek, mint amilyen a bérelhető számítási kapacitás (IaaS). A felhő-alapú megoldások alkalmazásával egyrészről az igénybe vevő az IKT-infrastruktúra üzemeltetéshez szükséges beruházástól, valamint az üzemeltetés által okozz további problémáktól is mentesülhet. 2019 elején egy kérdőíves felmérésre került sor, amelyben 498 válaszadó vett részt önkéntesen. A kutatás keretében azt vizsgáltam, hogy a magyarországi KKV-k körében milyen fejlettségi szinten áll az IKTinfrastruktúra kiépítése, ennek milyen információ-biztonsági következményei vannak, és a gazdálkodó szervezetek vezetése milyennek értékeli az IKT-infrastruktúra vállalati sikerességéhez történő hozzájárulását. A kérdőívben felmérésre kerültek a különféle felhő-alapú megoldások használata is. A publikációban a különféle felhő-alapú megoldások használatának gyakoriságára vonatkozó eredményeket összehasonlítom a régióban lebonyolított hasonló kutatásokkal, és megvizsgálom továbbá, hogy a felhő-alapú megoldásoknak van-e egyedileg kimutatható jótékony hatása a vállalati működésre, valamint a többféle felhő-alapú alkalmazások együttes használatakor azonosíthatóak-e szinergia hatások. A kutatás kvalitatív eredményei alapján és azoknak az értelmezést követően javaslatot teszek egy szélesebb körű elemzésre.

Резюме. Широкий спектр технологічних інновацій, які відбулися на рубежі тисячоліття і згодом стали загальнодоступними, докорінно змінили співвідношення між інфраструктурою інформаційних комп’ютерних технологій та бізнес-активністю суб’єктів господарювання. Особливо це стосується так званих первинних (вартісних) процесів. Технології, які фундаментально змінюють функціонування суб’єктів господарювання, сукупно називають технологіями «Індустрія 4.0». Однією із значущих груп цих технологій є так звані хмарні технології, завдяки застосуванню яких, користувач використовує переваги, що надаються інфраструктурою інформаційних комп’ютерних технологій через послугу від третьої сторони. Ці послуги можуть бути додатками, доступними через певний онлайн-інтерфейс (SaaS), різними елементами платформи (PaaS, прикладами яких є сервери додатків, віртуальні сервери тощо) або елементами інфраструктури, такими як оренда обчислювальної потужності (IaaS). Використовуючи хмарні рішення, з одного боку, користувач може бути звільнений від капіталовкладень, необхідних для роботи інфраструктури інформаційних комп’ютерних технологій, а також від додаткових проблем, викликаних роботою. На початку 2019 року проведено анкетування, в якому добровільно взяли участь 498 респондентів. У рамках дослідження проаналізовано рівень розвитку інфраструктури інформаційних комп’ютерних технологій серед угорських підприємств малого та середнього бізнесу, відповідні наслідки цього процесу для інформаційної безпеки та те, як керівництво суб’єктів господарювання оцінює внесок інфраструктури інформаційних комп’ютерних технологій в бізнес-успіх компанії. Анкетування досліджувало використання різних хмарних рішень. У публікації здійснено порівняльний аналіз результатів щодо частоти використання різноманітних хмарних рішень із аналогічними дослідженнями, проведеними в цьому напрямку, визначено, чи мають хмарні рішення індивідуально продемонстрований сприятливий вплив на діяльність компанії, а також ефект синергії, коли кілька хмарних додатків використовуються разом. На основі якісних результатів дослідження та після їх опрацювання запропоновано більш широкий аналіз даних процесів.
Використання хмарних рішень та аналіз їх пливу на угорський малий та середній бізнес
A magyarországi KKV-k által alkalmazott felhő-alapú megoldások és annak hatásainak elemzése
https://aab-economics.kmf.uz.ua/aabe/issue/view/3
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00012366
Keywords: ICT-Infrastructure; Industry 4.0; IaaS; for-profit organizations; research; SaaS; PaaS